Exploring the Workflow of Products’ Return Management in B2B Companies - Rocha, Joana; Babo, Rosalina (Bobcatsss, 2023)
The growing demand for new products also increases the market supply. However, with high number of products released in the market each year, consumers may have a difficult time in finding if a particular product is exactly what they need. Therefore, companies need to formulate return policies in case the consumer intends on returning the product. When companies have consumer return policies, it draws more customers, helps to stay competitive, and the consumer can be more at ease to order a product. According to Zailani et al. (2017, p. 24), product returns can be considered as “reverse logistics”, since it involves both logistics and “products’ reverse flows”. The products’ return can have several reasons, namely “product failure, damaged product, wrong delivery, incomplete shipments” and others (Batarfi et al., 2017; Lee, 2015, p. 50; Xu et al., 2018; Zailani et al., 2017). According to Lee (2015), the number of consumer product returns have been increasing along the years, even though there has been an overall improvement in the products’ quality. Therefore, the companies need to be able to manage the increased flow of these returns. The products’ return process involves several activities such as product recovery and processing, return organisation and reverse logistics (Russo et al., 2016). Managing this flow of information, as well as all the communication between the stakeholders, is very important and needs to be carefully handled (Guide et al., 2006; Lee, 2015; Ramírez, 2012; Russo et al., 2016). The company’s ability to perform the product return management and deliver fast decisions to the consumer can help them become a competitive advantage and increase customer loyalty. In Business-to-Business (B2B) context, the costumers are in lower number which in turn will strengthen the business relationship with them. However, the “average transaction value is higher” than in the Business-to-Consumer (B2C) market and therefore the product return management has a greater impact (Lesmono et al., 2020; Russo et al., 2016, p. 890) This study will compare the product return process between B2C companies and B2B companies, as well as look at the common practices used by these companies. It will also explore how these companies manage their consumer product returns, the product returns phases and main reasons for returns.